Bolt pre-load CAE analysis and validation: FEA simulation of hex bolt tightening torque for IDU assembly of 2-wheeler in MSC Nastran and practical validation. (2023) - Patne, Sachin; Karale, Ajinkya; Mohankumar, V.; Rane, Sandeep
Abstract: In any machine or automotive product, different nuts, bolts and other types of fasteners are used during assembly of the different parts. It is required to properly define the fastening loads or torques during the fastening application. In certain product assembly being manufactured and assembled by Varroc Engineering ltd, it is required to find out the exact tightening torque of the bolt as it could crack the product if the torque applied beyond certain limit. The product is IDU. In this we have done the bolt preload analysis in MSC FEA (Patran) software. Firstly, we found the allowable clamping force by analytical method. Then we performed bolt pre-load analysis to find the stress and displacement values which could be induced due to the certain tightening torque. Then we tested the part for same into lab and validated the results. Due to this simulation, we have been able to understand the behavior of the part under different bolt tightening torque values and thus it has enabled the designer to finalize the tightening torque values. Same concept of simulation is being applied now for tightening torque problems of different application.